Український правопис: історія та сучасність - Скрипкін, А. А. (ХНУРЕ, 2019)
Іп this article, we l'amiliarized ourselves with the Ukrainian spelling and the history of the Ukrainian language. We leamed the main stages of the development of spelling and the periods into which they are divided. Despite ail the difficulties and prohibitions Ukrainian spelling continues to be improved